Studi Toksikologi Biokimia : Dampak Senyawa Beracun Terhadap Proses Metabolisme Seluler dan Kesehatan Manusia - David Valentino Iskandar; Karina Sella Juwitasari; Erlanda Islami Pasha; Elsa Trisna Sari; Liss Dyah Dewi Arini (Student Scientific Creativity Journal, 2025)
Biochemical toxicology studies are disciplines that study the impact of toxic compounds on biochemical processes in the human body. Toxic compounds, whether from the environment, industrial chemicals, drugs, or natural products, can interfere with cellular metabolic mechanisms and potentially cause damage to organs or body systems. This study aims to analyze how toxic compounds interact with biomolecules, such as proteins, enzymes, and nucleic acids, which play a role in cellular metabolic processes. Disruption of metabolic enzymes can affect key metabolic pathways, such as energy synthesis, detoxification, and homeostasis regulation. These toxic impacts can contribute to the development of acute and chronic diseases, including liver, kidney, nervous system disorders, and cancer. In this study, we also discuss the detoxification mechanisms involving enzymes such as cytochrome P450 and glutathione-S-transferase in reducing the toxic effects of these compounds. A deeper understanding of toxic interactions and their impact on cellular metabolism is essential in developing preventive and therapeutic strategies for poisoning or toxicity-related diseases. This research is expected to provide insight into the development of more effective drugs and medical approaches in overcoming the effects of toxic toxins on humans.